Application of Lee Model Curve on Fitting of Discharge Current Curve of Plasma Focus Device - Gautam, Prakash (Advances in Engineering and Technology: An International Journal, 2021)
A dense plasma focus is a table top machine producing a short-lived extremely popular plasma and cause fusion. Lee Model Code is a computer-based visual basic simulation package, which was successfully utilized in the plasma focus devices. The dynamics of plasma focus discharge is quite complicated, so to review and simplify the complication Lee Model couples electrical circuit with the plasma focus dynamics, radiation and therefore the thermodynamics. This enables us to simulate all of the gross focus properties. In this paper the numerical experiments are carried out to compute the current trace as a function of time for plasma focus (PF) device NX2. Results obtained by the numerical experiments are compared with the published laboratory measured data. This current fitting is completed to get the model parameters.